Pengaruh Stres Kerja Dan Motivasi Terhadap Kinerja Perawat RSUD dr.Rasidin Padang - Indah Janurman; Henny Sulistianingsih (GLOBAL SCIENTS PUBLISHER, 2025)
The purpose of this study was to examine the effect of work stress and motivation on the performance of nurses at RSUD dr. Rasidin Padang. Work stress and motivation are factors that can affect the level of employee performance, including nurses. This study uses a quantitative approach. The sample in this study consisted of 136 nurses. The analysis technique in this study is the level of respondent achievement (TCR). Validity and Reliability Test. Normality Test, Multicollinearity Test, Heteroscedasticity Test, Multiple Linear Regression Analysis, t-test. F Test and Determination Coefficient (R2)